Assessing the performance of university departments using data envelopment analysis - Mohamad, N.; Said, F. (2009)
An efficient use of resources is important in the administration of institutions of higher learning. In this study, data envelopment analysis, DEA, is used to measure the relative efficiency of academic departments of a premier public university, the oldest in the country. Selected input and output indicators are examined and measured utilizing the academic performance of research, teaching and publication. A linear programming based output-oriented DEA models under the assumptions of constant returns to scale, CRS and variable return s to scale, VRS are formulated to compute the relative efficiency of departments of different disciplines. Sources of inefficiency for the inefficient units are computed by utilizing the dual values of their respective peer units. This helps to identify targets and areas where more effort should be devoted to improve the efficiency of the departments.